Optimization of The Aqueous Enzymatic Extraction (AEE) of Rice Bran Oil With Cellulase Using Response Surface Methodology - Astrilia Damayanti; Bayu Triwibowo; Megawati Megawati; Ahmed Tessario Ekanuramanta; Harianingsih Harianingsih; Kevin Thomas; Nurul Huda; Nuryoto Nuryoto (Universitas Negeri Semarang, 2023)
Rice Bran Oil (RBO) is an oil extracted from rice bran with unsaturated fat content according to World Health Organization (WHO) standards. The enzymatic extraction process of rice bran for oil extraction using cellulase enzymes is considered effective because it is capable of producing oil. Parameters of temperature and incubation time have an influence on the yield of oil produced. So that research is needed regarding the optimum conditions of the enzymatic extraction process including temperature and incubation time on the yield and levels of FFA RBO.Software Design Expert was used in this study to optimize RBO extraction with cellulase using the Response Surface Methodology (RSM) method in the Central Composite Design (CCD) factorial experimental design. The selected independent variables consisted of incubation temperatures, namely 35, 50, and 65 0C and incubation time for 2, 3, and 4 hours. The results show that the RBO yield is 1.7% and the minimum target for FFA levels is 8.4% at a temperature of 51.5 0C with an incubation time of 4 hours. Processing data with Design expert software produces an analysis of ANOVA experimental data. Incubation time has a significant level (p0.05) on RBO yield and incubation temperature has a significant level (p0.05) on RBO FFA.